Comparative clinical efficacy of acupuncture combined with manipulation and other non-pharmacological interventions in the treatment of lumbar disc herniation: a prospective, multi-arm, randomized, open-label, blinded endpoint trial - Fudong Shi; Haibao Wen; Yuzhang Liu; Zuoxu Li; Jiao Jin; Ning Liu; Guojun Wang; Chun Chen; Yadi Feng; Hai Lin; Shimin Zhang (Frontiers in Medicine)
ObjectiveTo compare the clinical efficacy and safety of four intervention methods—traditional Chinese manipulation combined with acupuncture, acupuncture alone, manipulation alone, and traction—for the treatment of lumbar disc herniation (LDH).MethodsA prospective, multi-arm, randomized, parallel-controlled clinical trial was conducted between July 2021 and June 2024. A total of 240 eligible LDH patients were randomized into four groups (60 patients per group) in a 1:1:1:1 ratio: manipulation combined with acupuncture group, manipulation group, acupuncture group, and traction group. Each treatment lasted for 3 weeks. Changes in Visual Analog Scale (VAS) and Japanese Orthopedic Association (JOA) scores were recorded before treatment, at 1 and 3 weeks during treatment, and at 1 and 3 months post-treatment. Adverse events were also monitored.ResultsA total of 210 patients completed the follow-up. At the 3-week (day 21) and 3-month (day 111) follow-ups, the acupuncture + manipulation group showed the most significant improvements, with VAS scores decreasing by 63.34% and 68.30% and JOA scores increasing by 55.17% and 58.33%. The acupuncture group showed VAS score reductions of 55.04% and 59.29% and JOA score increases of 44.52% and 48.29%. The manipulation group reported VAS score reductions of 51.73% and 55.02% and JOA score increases of 41.16% and 45.27%. The traction group demonstrated the least improvement, with VAS scores decreasing by 43.25% and 45.73% and JOA scores increasing by 30.55% and 33.97%. Statistical analysis indicated that the acupuncture + manipulation group had significantly better improvements in VAS and JOA scores than the other three groups during treatment and follow-up periods (P < 0.05). There were no significant differences between the acupuncture and manipulation groups (P > 0.05), while the traction group showed significantly less improvement compared to the other groups (P < 0.05).ConclusionThis study demonstrates that acupuncture combined with spinal manipulation significantly reduces pain and improves lumbar function in LDH patients compared to other tested interventions. The symptom relief rate was significantly higher in the acupuncture + manipulation group compared to the acupuncture, manipulation, and traction groups.Clinical trial registrationhttps://www.chictr.org.cn/index.aspx, identifier ChiCTR2200058598.